The Future of Learning: Integrating Robotic Efficiency for Enhanced Educational Efficacy - Massaty, Muhammad Hassan; Budiyanto, Cucuk Wawan; Tamrin, A.G.; Fahrurozi, Slamet Kurniawan (Journal of Global Hospitality and Tourism Technology, 2024)
The Covid-19 pandemic has posed learning barriers for communities in Indonesia and around the world. It has disrupted normal teaching and learning activities, necessitating the adoption of distance learning. Students face challenges during distance learning, including low motivation to succeed and complete online classes, as well as difficulty in handling encountered problems or difficulties. Robotics was chosen as a learning medium because it has been proven to stimulate self-efficacy. The development of self-efficacy among students is crucial in distance learning implementation as it can help overcome barriers that arise during the learning process. This research aims to implement robotics media in distance learning while considering media accessibility and self-efficacy. The research methodology employed is a field case study with qualitative descriptive data analysis techniques. The results of the study indicate that with the use of robotics media, student enthusiasm level reached 92%, and 92% of students fully comprehended the presented learning materials. The implementation of distance learning using robotics media was highly successful, with 92% of students expressing increased diligence in their studies, and 96% of students striving to improve their grades. Student self-efficacy was also relatively high, with 88% of students showing confidence in their ability to engage in learning. The use of robotics media aided students in distance learning, with a 100% completion rate and satisfactory achievement results. Additionally, it was found that the inclusion of illustrations had an impact on students' confidence in completing tasks correctly and accurately. more tangible and accessible.